2006
DOI: 10.1016/j.icesjms.2005.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced differences in the essential fatty acid (EFA) compositions of larval Atlantic cod (Gadus morhua L.) with reference to possible effects of dietary EFAs on larval performance

Abstract: We studied the performance of cod rearing in which live feed was given under three different essential fatty acid (EFA) enrichment regimes, using commercially available live-feed enrichments. We assessed the fatty acid profile [docosahexaenoic (DHA), eicosapentaenoic (EPA), and arachidonic acid (AA)] in larval somatic tissue, relative to its amounts in both rotifers and Artemia as well as to larval performance. Overall, percentage lipid level of each experimental diet for the trial was approximately 50%. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Larval AA levels seemed to be more conservative, with only larvae from the AlgaMac treatment having higher levels of AA at 59 dph than at the start of the experiment. Cutts et al (2006) observed similar trends in Atlantic cod larvae fed rotifers and Artemia enriched differently. Despite the different enrichments, Atlantic cod DHA levels were approximately six times lower at 50 dph in all treatments, when compared to the period where the larvae were still feeding on rotifers (at 10 or 22 dph).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Larval AA levels seemed to be more conservative, with only larvae from the AlgaMac treatment having higher levels of AA at 59 dph than at the start of the experiment. Cutts et al (2006) observed similar trends in Atlantic cod larvae fed rotifers and Artemia enriched differently. Despite the different enrichments, Atlantic cod DHA levels were approximately six times lower at 50 dph in all treatments, when compared to the period where the larvae were still feeding on rotifers (at 10 or 22 dph).…”
Section: Discussionsupporting
confidence: 66%
“…Despite the different enrichments, Atlantic cod DHA levels were approximately six times lower at 50 dph in all treatments, when compared to the period where the larvae were still feeding on rotifers (at 10 or 22 dph). Atlantic cod AA levels were more stable, with larvae from all treatments exhibiting similar levels throughout the entire trial (Cutts et al 2006). Preferential accumulation of AA and reduction of DHA levels have also been observed in Atlantic halibut, Hippoglossus hippoglossus (Hamre et al 2002), and Senegal sole, Solea senegalensis, larvae (Villalta et al 2005) fed Artemia.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The conclusion might then be that the percentage fraction of DHA in the diet determined the enrichment levels of DHA in PL of the rotifers. An alternative explanation might be that a lipid emulsion, which constitutes mainly lipids, is more poorly assimilated and therefore metabolically less efficient for transferring DHA to rotifer PL than a slightly more complete enrichment feed, with some proteins added (13%, Table 1) and with high DHA level (Cutts et al, 2006). The enhanced efficiency might be a combination of these effects, and a Multigain-type diet would then in all events be most efficient for PL enrichment of DHA and HUFA.…”
Section: Enrichment Dietmentioning
confidence: 99%